2022
DOI: 10.3389/falgy.2022.981126
|View full text |Cite
|
Sign up to set email alerts
|

Roles of type 1 regulatory T (Tr1) cells in allergen-specific immunotherapy

Abstract: Allergen-specific immunotherapy (AIT) is the only causative treatment for allergic diseases by modification of the immune response to allergens. A key feature of AIT is to induce immunotolerance to allergens by generating antigen-specific regulatory T (Treg) cells in allergic patients. Type 1 regulatory T (Tr1) cells and forkhead box protein 3 (Foxp3)-expressing Treg cells are well known among Treg cell subsets. Foxp3 was identified as a master transcription factor of Treg cells, and its expression is necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 175 publications
0
11
0
2
Order By: Relevance
“…IL-10 is crucial for effector T cell anergy and for allergen-specific IgG production [196]. The percentages of IL-10-producing CD49b + LAG-3 + Tr1 cells in allergic patients are significantly lower than in healthy subjects [97], which significantly increase after successful AIT [197]. It was suggested that the IL-10-related transcription factor E4BP4 plays a regulatory role, as its mRNA and the numbers of Tr1 cells were elevated in blood of patients treated with SCIT [198].…”
Section: Allergen-specific Immunotherapymentioning
confidence: 99%
“…IL-10 is crucial for effector T cell anergy and for allergen-specific IgG production [196]. The percentages of IL-10-producing CD49b + LAG-3 + Tr1 cells in allergic patients are significantly lower than in healthy subjects [97], which significantly increase after successful AIT [197]. It was suggested that the IL-10-related transcription factor E4BP4 plays a regulatory role, as its mRNA and the numbers of Tr1 cells were elevated in blood of patients treated with SCIT [198].…”
Section: Allergen-specific Immunotherapymentioning
confidence: 99%
“…ACT with Treg cells can be achieved using three methods: polyclonal Treg cells without antigen stimulation, antigen-stimulated and expanded Treg cells, and Treg cells with a genetically engineered chimeric antigen receptor. Adoptive transfer of Treg cells has been proposed to treat T cell-mediated immune diseases including organ transplant rejection, autoimmune diseases, and allergic diseases [ 134 , 135 ]. However, human clinical studies using the adoptive transfer of ex vivo expanded Treg cells for AD or other allergic diseases have not been conducted.…”
Section: Immunomodulatory Strategies Activating Regulatory T Cells Fo...mentioning
confidence: 99%
“…Activated Treg cells release IL-10 and suppress Th2 cell-mediated allergic inflammation. However, there are still controversies regarding the main subpopulation of Treg cells mediating therapeutic effects involved in allergen immunotherapy (CD4 + Foxp3 + Treg cells and/or CD4 + Foxp3 - IL-10 + Treg cells) ( 91 ).…”
Section: Evidence Supporting Activation Of Treg Cells By Polyvalent I...mentioning
confidence: 99%
“…Expansion of CD4 + Foxp3 + Treg cells in the peripheral blood has been reported in patients with autoimmune diseases after intravenous administration of high-dose (1~2 g/Kg of body weight) heterologous IVIg ( 60 , 65 , 93 ). Continuous regular intravenous infusion of a high dose of polyvalent human IgG is needed to achieve a long-term clinical improvement in patients with autoimmune diseases ( 60 , 91 , 93 ). This requirement of continuous treatment has been attributed to the low concentration and low affinity of natural anti-idiotype antibodies to pathogenic autoantibodies contained in IVIg ( 17 ).…”
Section: Evidence Supporting Activation Of Treg Cells By Polyvalent I...mentioning
confidence: 99%